THE INFLUENCE STUDENTS’ LEARNING STYLE PREFERNCES TO THEIR SPEAKING ACHIEVEMENT - Ilma, Ridha; Ria, Nita (English Community Journal, 2019)
This study aimed to find out whether or not there was a significant correlation between students’ learning style preference and their speaking achievement. The data were collected by distributing questionnaire sheets and testing a speaking achievement test for 55 students. It used correlational study. There were two kinds of variables in this study, predictor and criterion variables. The predictor variable was students’ learning style preference (x), and the criterion variable was students’ speaking achievement (Y). The sample was divided into two groups; experimental and control group. There were 30 students for experimental group (VIII.6) and 25 students in a control group (VIII. 1). Pearson product moment coefficients correlation and regression analysis were used to find out whether or not there was a significant relationship between students’ learning styles preference toward speaking achievement of SMPN 12 Palembang. Only students’ learning style in the pre-test of the experimental group was significantly correlated to their speaking achievement. It was also supported by the regression analysis, learning style preference gave 19.4 % contribution to speaking achievement. The speaking test of post-experimental, pre-control, and post-control group was not correlated significantly to learning style preference. And contribution also vice versa. Those three scores from the speaking test did not contribute significantly to learning style preference.